2017
DOI: 10.1002/ana.24941
|View full text |Cite
|
Sign up to set email alerts
|

Brain regions essential for word comprehension: Drawing inferences from patients

Abstract: Lesion-deficit association studies are important as they can reveal brain regions essential for specific functions, but sometimes appear to yield conflicting results. We aimed to show how pitfalls of lesions studies can be avoided, and converging results obtained, illustrating from studies of the role of posterior superior temporal gyrus in auditory word comprehension. We review published lesion studies on auditory comprehension and present new data from both acute and chronic stroke that address weaknesses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 45 publications
4
32
1
Order By: Relevance
“…The main differences were that functional results included the left lateral/medial middle and inferior temporal gyri and left anterior fusiform gyrus, while anatomical results were largely restricted to the superior temporal gyrus, but extended into the posterior superior temporal gyrus. These findings are consistent with the classic localization of auditory comprehension to the temporal lobe, as shown by prior stroke lesion studies Hillis et al, 2017) and fMRI studies of healthy controls (Price, 2012). The fact that the functional results extend more ventrally into the temporal lobe likely relates to poor anatomical lesion coverage in that region.…”
Section: Functional Anomaly Map Signal Relates To Behavior In Both Lesupporting
confidence: 90%
“…The main differences were that functional results included the left lateral/medial middle and inferior temporal gyri and left anterior fusiform gyrus, while anatomical results were largely restricted to the superior temporal gyrus, but extended into the posterior superior temporal gyrus. These findings are consistent with the classic localization of auditory comprehension to the temporal lobe, as shown by prior stroke lesion studies Hillis et al, 2017) and fMRI studies of healthy controls (Price, 2012). The fact that the functional results extend more ventrally into the temporal lobe likely relates to poor anatomical lesion coverage in that region.…”
Section: Functional Anomaly Map Signal Relates To Behavior In Both Lesupporting
confidence: 90%
“…Thus in the current paradigm, we expected facilitation to manifest as lower amplitudes for the semantically related condition than the unrelated condition and even lower ones for the identity condition, which involves repetition of the same word. Exactly this pattern was observed in left superior temporal cortex at 180-335 ms, which conforms with the localization of lexical access both in space (Hickok & Poeppel, 2007;Hillis, Rorden, & Fridriksson, 2017;Lau, Phillips, & Poeppel, 2008) and time ("lemma selection" in Indefrey, 2011;Indefrey & Levelt, 2004). Thus, this effect has a straightforward interpretation in terms of spreading activation between semantically related lexical representations.…”
Section: Facilitation In Word Reading At 180-335ms Centered In Left Ssupporting
confidence: 81%
“…There is evidence from both lesion studies and functional imaging studies that there is a circuit of gray matter regions and white matter tracts that supports word comprehension, 36 which includes left pSTG as well as middle and inferior temporal gyri, temporal pole, and tracts that connect them. 19,[22][23][24][25][26][27] However, our results do indicate that left pSTG and retrolenticular white matter are critical for linking the spoken word to one of a set of semantically related meanings.…”
Section: Discussioncontrasting
confidence: 67%
“…However, previous studies that have separately evaluated areas critical for nonverbal semantics (e.g., with picture-picture association) have found that the anterior temporal lobe is associated with nonverbal semantics, whereas pSTG remain associated with word comprehension after controlling for performance on picture-picture association. 27,36 FUTURE DIRECTIONS Additional investigations are planned to identify areas of acute tissue dysfunction (infarct and/or hypoperfusion) that are associated with phonological errors in naming. It is possible that we did not have adequate power to identify these areas, after correcting for lesion volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation